Krzywizna i Wydłużenie Osi Sprężystych Cylindrów Mimośrodowych pod Działaniem Ciśnienia Wewnętrznego - Albińska, D. (Engineering Transactions, 1970)
A thick-waller elastic eccentric cylinder is hare considered, subjected to the action to a uniform internal pressure p. For this purpose known solutions were utilized for a cylinder under the conditions for a plane state of deformation when a certain bending moment M and a longitudinal force N are acting upon it. To solve the problem of pure internal pressure, it is necessary, in accordance with the principle of superposition, to apply additionally a bending moment (M) and a longitudinal force (–N). In the paper, formulae are deriverd for these quatities by performing corresponding integration in bipolar coordinates. Further, the curvature x and elongation e0 , are determined for the axis of the cylinder under consideration in the case of pure internal pressure, which on the basis of the principle of superposition makes it possible to solve also any complex case. A numerical example gives the distribution of stresses in the eccentric cylinder under the action of pure internal pressure.